Enhancing competitiveness in the peruvian textile industry through lean manufacturing: a case study on reducing defects and improving efficiency - Touzett Cabellos, Antonio Carlos (2024)
The Peruvian textile sector, representing 7.2% of the manufacturing GDP and providing approximately 422,000 jobs annually, faces significant challenges due to high defect rates and process inefficiencies. This study aimed to develop a Lean Manufacturing Model to address these issues by integrating Lean tools such as 5S, Total Productive Maintenance (TPM), and standardized work processes. The proposed model focused on diagnosing current operational inefficiencies, designing strategic solutions, implementing these improvements, and continuously analyzing performance to ensure sustainability. The results demonstrated notable improvements, including a reduction in the defect rate from 18% to 5%, an increase in 5S audit scores from 65% to 81%, and a decrease in the rework rate from 20% to 7%. These outcomes highlighted the model's effectiveness in enhancing productivity, quality, and operational efficiency, ultimately contributing to the competitiveness of the Peruvian textile industry.